1996
DOI: 10.1007/bf00702349
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of O-glycosylation by bovine colostrum UDP-GalNAc: polypeptide ?-N-acetylgalactosaminyltransferase using synthetic glycopeptide substrates

Abstract: The factors determining glycosylation of mucin type glycoproteins are not well understood. In the present work, we investigated the role of the peptide moiety and of the presence of O-glycan chains on O-glycosylation by UDP-GalNAc: polypeptide alpha-N-acetylgalactosaminyl-transferase (ppGalNAc-T). We used purified ppGalNAc-T from bovine colostrum and a series of synthetic glycopeptide and peptide substrates most of which contained sequences derived from the tandem repeat region of MUC2 mucin. The rate of incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…According to this concept, the site specificity of initial O-glycosylation would not merely be ruled by the peptide sequence around putative target sites. Evidence for negative effects on vicinal sites induced by mono-or disaccharide substituents has previously been reported for a series of glycopeptide substrates based on the MUC2 repeat peptide (12). Another in vitro glycosylation study indicated that positive regulatory effects on vicinal sites could also be responsible for the accelerated GalNAc transfer (7).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…According to this concept, the site specificity of initial O-glycosylation would not merely be ruled by the peptide sequence around putative target sites. Evidence for negative effects on vicinal sites induced by mono-or disaccharide substituents has previously been reported for a series of glycopeptide substrates based on the MUC2 repeat peptide (12). Another in vitro glycosylation study indicated that positive regulatory effects on vicinal sites could also be responsible for the accelerated GalNAc transfer (7).…”
mentioning
confidence: 80%
“…The samples were diluted with incubation buffer to give a total volume of 210 l prior to ultrafiltration through ultrafree MC membranes (Millipore, Eschborn, Germany) with a nominal cut-off of 10 kDa. Kinetic parameters were calculated by double reciprocal LineweaverBurk transformations at four substrate concentrations using assay conditions described by Brockhausen et al (12).…”
Section: Enzymatic Assaysmentioning
confidence: 99%
“…where the specificities of both the ppGalNAc and core 1 transferases were proposed to be affected by steric effects of neighboring glycosylated residues (22,23,32,33,58,59).…”
Section: Discussionmentioning
confidence: 99%
“…1 To date, 10 ppGalNAc transferase isoforms have been described (9 -16). Although each transferase has not been fully characterized, their peptide substrate specificities vary within the family (11,(17)(18)(19)(20)(21); many show sensitivity to prior glycosylation, and others require prior addition of GalNAc for activity (9,14,20,(22)(23)(24). The expression of ppGalNAc transferase isoforms with different peptide and/or glycopeptide specificities therefore represents the first step in the regulation of O-glycan structure by peptide sequence in vivo.…”
mentioning
confidence: 99%
“…ppGal NAcT-1 exhibits a selective preference for some polypeptide sequences (7,16,60), further suggesting that a key function is likely provided by its activity among cells of intact organisms. The ppGalNAcT family of glycosyltransferases initiates coretype O-glycan formation, primarily consisting of core 1, core 2, core 3, and core 4 O-glycan subtypes that may be elaborated further by glycan linkages, contributing to selectin ligand-dependent control of leukocyte trafficking, regulation of CD8 ϩ T-cell apoptosis, and sensitivity to colitis and preventing the onset of Tn syndrome (11,27,42,59,65).…”
mentioning
confidence: 99%